APCs in the Wild: could monitoring and tracking of OA payments help speed up the transition to OA? - Lucraft, Mithu (Septentrio Conference Series, 2020)
See RECORDING (starts at 00:19:05). Accelerating progress towards full and immediate open access (OA) is reliant on being able to source adequate funding to cover the costs of gold OA. Monitoring and tracking OA payments has created a complex and challenging role for institutions, but is crucial in order to understand the complete picture of the cost of OA. Whilst some institutions have developed methods to monitor OA payments, there remain a high number of "APCs in the wild", or APC payments whose origins are difficult to track. In this presentation we will summarise research Springer Nature has undertaken to explore the tracking and monitoring of APC payments, including interviews and a survey of global librarians, and data from Springer Nature authors to better understand the sources of APC funding, and the motivations and challenges concerning the monitoring of APCs. We will focus on feedback from institutions on the routes to implement better tracking, and on the noted benefits of being able to do so in enabling a faster transition to OA.